2021
DOI: 10.1155/2021/1838903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Hydroethanolic Root Extract and Solvent Fractions of Cyphostemma adenocaule (Steud. ex A. Rich) Descoings ex Wild & Drummond on Cell-Mediated Immune Response and Blood Cell Count in Mice

Abstract: Introduction. Cyphostemma adenocaule (Steud. ex A. Rich) Descoings ex wild & Drummond (Vitaceae) has been used in traditional medicine for the management of various immunological and hematological disorders in different areas of Ethiopia and the rest of the world. In Ethiopia, the plant is used for the management of enlarged spleen, rabies virus, helminthic infection, snake bite, and various types of tumors. Objective. To evaluate the effect of hydroethanolic root extract and solvent fractions of Cyphostem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Based on the reported safety profile of the crude extract and solvent fractions at a limit dose of 2000 mg/kg; 100, 200, and 400 mg/kg of crude extract and solvent fractions were taken as treatment doses [ 15 ]. Thus, Mice were randomly grouped into sixteen groups for the carbon clearance test ( Table 1 ) and twelve groups for Humoral antibody titer ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the reported safety profile of the crude extract and solvent fractions at a limit dose of 2000 mg/kg; 100, 200, and 400 mg/kg of crude extract and solvent fractions were taken as treatment doses [ 15 ]. Thus, Mice were randomly grouped into sixteen groups for the carbon clearance test ( Table 1 ) and twelve groups for Humoral antibody titer ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…C. adenocaule is reported to for its antiplasmodial [ 13 ], antioxidant [ 11 ], anthelminthic [ 14 ], and anti-inflammatory activities [ 11 ]. The plant also has a proliferative effect on blood cells in mice models [ 15 ]. The traditional medicinal claims of the plant might be due to the immunomodulatory effect of its bioactive metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…( Figure 1 ) is one of the most prevalent vegetable plants grown in many parts of Africa, i.e., Ethiopia, Angola, Nigeria, Eritrea, Ghana, Uganda, Congo, Senegal, Malawi, and Mozambique [ 7 , 8 ]. In Ethiopia, the plant has different vernacular names, such as Hareg Temen (Tigrinya), Aserkuh Aserkush (Amharic), and Hida Bofa (Afan Oromo) [ 9 ]. In Tigray, Northern Ethiopia, the fresh roots of the plant have long been used against rabies, snake bite, and wound healing [ 10 ] and traditional healers around Gondar, Ethiopia, use the boiled root of C. adenocaule with milk and drink it to treat rabies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scores of research studies showed that plant EOs from the genus of the two plants possess chemical compounds with broad pharmacological and biological properties [14]. In Ethiopia, the genus Cyphostemma have long been used for the treatment of rabies, snake bites and skull wounds, and also possess antimalarial, anticancer, antitumor and antihelminthic properties [15]. EOs of the genus Ziziphus have also been used in folk medicine against some diseases, such as diabetes, skin infections, diarrhea, fever, obesity and digestive disorders [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cyphostemma adenocaule (Figure 1A) which belongs to the Vitaceae family, is locally called Aserkuh Aserkush (Amharic), Hareg Temen (Tigrinya) and Hida Bofa (Afan Oromo), and is traditionally used to treat urinary tract infections, syphilis, bloody diarrhea, rabies and snake bite [12], helminthic infections and anthrax [15]. Previous in vitro biological studies also revealed that, the plant possess anticancer [18], antioxidant [19], antibacterial [20], antitumor [18], antiplasmodial [12] and deworming [21] activities.…”
Section: Introductionmentioning
confidence: 99%